Medicina de precisión y serendipia genética: hallazgos secundarios al realizar secuenciación de exomas - Sepúlveda B., Francisca; Pardo V., Rosa Andrea (Revista Hospital Clínico Universidad de Chile, 2025)
This review examines the current state of secondary findings (SF) in clinical exome sequencing, including their frequency, clinical relevance, ethical implications, psychological impact, and future perspectives in preventive and personalized medicine. A comprehensive literature review was conducted analyzing recent publications on SF in exome sequencing, including prevalence studies, clinical management guidelines, ethical frameworks, and psychological impact assessments. The prevalence of SF ranges from 1.1% to 8% across different populations, with the American College of Medical Genetics and Genomics (ACMG) expanding its recommended gene list for reporting SF from 56 genes in 2013 to 81 genes in 2023. Studies indicate that while SF disclosure can initially cause psychological distress, most patients value this information for its preventive potential. Technical challenges include variable coverage of SF genes across laboratories and limitations in detecting copy number variants, while cost-effectiveness studies suggest modest healthcare cost increases associated with SF disclosure. Secondary findings in exome sequencing offer significant opportunities for preventive medicine while presenting complex clinical, psychological, and ethical challenges, where standardization of practices, improved analytical tools, and focus on education and equity are crucial for maximizing their benefits in genomic medicine.